2015
DOI: 10.1111/obr.12271
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric non‐alcoholic fatty liver disease: an overview

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a progressive disease that encompasses a spectrum of liver diseases, ranging from simple steatosis to non-alcoholic steatohepatitis (NASH). Data related to survival in children are scarce, but these data firmly associate NAFLD with higher risks of hepatic and non-hepatic morbidities and mortalities compared with the general population. More recently, the association between NAFLD and cardiovascular disease among children has increasingly been recognized. Given that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 144 publications
1
36
1
1
Order By: Relevance
“…The discrepancies between adult NAFLD and the corresponding paediatric and adolescent type were recognized and could be attributed to confounders of disease, including dietary habits, lifestyle routines, disease duration, and comorbidities. These factors could play less of a role in early‐onset disease, which is more vulnerable to variation in the genetic constitution . Thus, after finding the significant association between the I148M polymorphism and NAFLD in the general population, this exploratory meta‐analysis was performed to provide a unique perspective on the accumulated evidence regarding the magnitude of the risk and severity of early‐onset NAFLD and MetSs.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancies between adult NAFLD and the corresponding paediatric and adolescent type were recognized and could be attributed to confounders of disease, including dietary habits, lifestyle routines, disease duration, and comorbidities. These factors could play less of a role in early‐onset disease, which is more vulnerable to variation in the genetic constitution . Thus, after finding the significant association between the I148M polymorphism and NAFLD in the general population, this exploratory meta‐analysis was performed to provide a unique perspective on the accumulated evidence regarding the magnitude of the risk and severity of early‐onset NAFLD and MetSs.…”
Section: Introductionmentioning
confidence: 99%
“…8 The clinical burden of NAFLD is not limited to liver-associated morbidity and mortality, but NAFLD is also associated with elevated risk to develop type 2 diabetes and cardiovascular disease. 9 Preliminary evidence suggests a link between NAFLD and decreased BMD. 10,11 However, the majority of the studies have been conducted in Asian populations, and in adults 12 and adolescents, 13,14 while the information in children is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that the entire spectrum of NAFLD also occurs during childhood (Molleston et al, 2002;Kleiner and Makhlouf, 2016). Concurrent with childhood obesity, NAFLD has developed into a serious concern in pediatric clinical practice and has become a significant health burden in adolescence (AlKhater, 2015). An autopsy-based study estimated the overall prevalence of NAFLD in the American pediatric population at 9.6%, which increased to 17.3% in adolescents from 15 to 19 years old (Schwimmer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%